Bimbingan dan Konseling dalam Perspektif Pendidikan: Aktualisasi Peran Bimbingan dan Konseling dalam Pendidikan Indonesia - Eni Rakhmawati (Fakultas Ilmu Tarbiyah dan Keguruan, Institut Agama Islam Bakti Negara Tegal, 2023)
Education is a conscious and planned effort to create an atmosphere and learning process so that students actively develop their potential. Indeed, the existence of counseling guidance has a major function in developing human resources. All forms of deviations that we often hear today become a concern for the decline in social quality and character of this nation's generation in the future. The purpose of this study is to determine the importance of counseling guidance in the perspective of education and the role of guidance and counseling in education in Indonesia. The research method used is qualitative with the type of library research. The data reviewed in this paper is secondary data obtained through literature study. The subject of counseling is human, the existence of globalization has an impact on increasing human needs and desires to pursue various things that are offered and promise something better. The result of this research is that counseling guidance is a process of providing assistance provided by an expert (mentor teacher) continuously to an individual or a group of individuals (students), to prevent or overcome problems that arise with various potentials owned, so that they can achieve optimal development and can plan a better future, make adjustments to their environment and achieve their welfare. life. Cultural, psychological, educational and environmental aspects are important in the study of counseling and counseling guidance. Character building is one of the goals of national education. Schools from kindergarten to college have a central role in developing and instilling character values. Extra-curricular activities in schools that have been organized by schools are one of the good media for fostering the character of students.